The Offshore Drilling Industry and Rig Construction in the Gulf of Mexico - Kaiser, Mark J.; Snyder, Brian F.; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2013)
Jackups, semisubmersibles and drillships are the marine vessels used to drill offshore wells and are referred to collectively as mobile offshore drilling units (MODUs). MODUs are supplied through newbuild construction and operate throughout the world in highly competitive regional markets. The Offshore Drilling Industry and Rig Construction Market in the Gulf of Mexico examines the global MODU service and construction industry and describes the economic impacts of rig construction in the United States.   The industrial organization and major players in the contract drilling and construction markets are described and categorized. Dayrates in the contract drilling market are evaluated and hypotheses regarding dayrate factors are tested. Models of contractor decision-making are developed, including a net-present value model of newbuilding investment and stacking decisions, and market capitalization models are derived. Jackup construction shipyards and processes are reviewed along with estimates of labor, equipment, and material cost in U.S. construction. Derivation of newbuild and replacement cost functions completes the treatise.    The comprehensive and authoritative coverage of The Offshore Drilling Industry and Rig Construction Market in the Gulf of Mexico makes it an ideal reference for engineers, industry professionals, policy analysts, government regulators, academics and other readers wanting to learn more about this important and fascinating industry.
1.Mobile Offshore Drilling -- 2.The Five Offshore Rig Markets -- 3.Rig Dayrates and Utilization -- 4.Players and Market Structure -- 5.Empirical Analysis of the Factors Impacting Dayrates -- 6.Newbuild and Stacking Decision-Making -- 7.Factors That Impact Firm Value -- 8.Contractor Valuation Models -- 9.Construction Markets and Contracts -- 10.Jackup Design Primer -- 11.Jackup Rig Construction -- 12.Construction Cost Factors -- 13.Newbuild and Replacement Cost Functions -- 14.Jackup Rig Weight Algorithm -- 15.Labor and Material Requirements for Jackup Construction in the U.S.
Keywords: Energy policy; Energy and state; Engineering economics; Engineering economy; Energy Policy, Economics and Management; Engineering Economics, Organization, Logistics, Marketing